Upper and lower river physico-chemical characteristics of Pahang river : a baseline study - Mohd Azim, Abdul Halim (2012)
A study is carried out on physico-chemical characteristics, anions and heavy metal concentration in several upper and lower sites of Pahang River. Jelai River, Tembeling River, Temerloh, Kampung Belimbing, Kampung Temai and Pekan were chosen as the sampling site. Sampling activities is done once in two weeks for three months period. The physical and chemical characteristics analyses includes six water parameters including pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen and dissolved oxygen (DO). Common heavy metals such as lead, copper and cadmium are determined spectroscopically. Six anions are used as standard including fluoride, chloride, bromide, nitrate, phosphate and sulphate to determine the presence of anions in the samples. Phosphate is the only anion which is not detected in all the samples. In heavy metals analysis, only copper. is detected in the samples while cadmium and lead are not detected. The yalues of BOD and COD are increasing due to increasing demand of oxygen as the river flows to the lower part before discharging to the sea. Tembeling River shows the lowest value of TSS as the river is less turbid than other five rivers. DO in all water samples are decreasing due to decreasing of oxygen solubility in the lower parts of Pahang River.